High order approximation of degree nine and order eighteen - Abedallah Rababah (Journal of Inequalities and Applications, 2019)
Abstract In this paper, a method to approximate curves by polynomials of degree nine is presented. The resulting approximation has order eighteen. The method is applied to approximate a circular arc, and the error function is studied and characterized, and its extrema and zeros are derived.